Pengaruh Padat Tebar Tinggi Dengan Penggunaan Nitrobacter Terhadap Pertumbuhan Ikan Lele (Clarias Sp.) Effect of Stocking Density with Adding Nitrobacter on Growth of Catfish (Clarias sp.) - Fenlya Meitha Pasaribu; Syammaun Usman; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Catfish is one of the freshwater fishery commodities whose demand is increasing in Indonesia. Intensive cultivation is required to meet the market demand. Intensive cultivation can be done by optimizing the stocking density. This study aimed to determine the effect of added Nitrobacter with high stocking density system on the survival, height growth and weight growth of catfish (Clarias sp.) As well as to determine the maximum stocking density of catfish with the average length of 6 cm and 1.5 gram in average weight. 450 catfish were used. The study was conducted at Laboratory of Aquaculture, Water Resource Management, Faculty of Agriculture, University of Sumatera Utara, Medan in June until July 2016. The container were used are 9 aquarium size of 60 cm x 40 cm x 40 cm with a volume of 72 liters each aquarium. The parameters were observed during 42 days of observation are; survival, weight growth and length growth. During the study, fish were fed with artificial feed as much as 5% of body weight per day. The feeding frequency are 3 times a day which are at 10:00, 14:00, 18:00. This study used completely randomized design (CRD) with 3 treatments, those are stocking density of 600 individuals / liter (P1), 700 fish / liter (P2) and 800 fish / liter (P3) and repeated 3 times. The P1 treatment showed the best score at weight growth rate and length growth rate in the amount of 40,70 gram and 12,63 cm. The P3 treatment showed the lowest weight growth rate and length growth rate that is equal to 38,74 gram and 12,18 cm. Stocking density did not significantly affected the length growth rate, weight growth rate and survival of fish.Keywords : Clarias sp., Growth, Stocking Density, Survival